2019
DOI: 10.12669/pjms.35.4.194
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in Pakistan: A systematic review and meta-analysis

Abstract: Objective: The purpose of this study was assess the time trend of the prevalence of prediabetes and diabetes and risk factors associated with diabetes in Pakistan by using a systematic review and meta–analysis. Methods: A systematic literature search of Embase, PubMed, and the Cochrane library was carried out between January 1, 1995 and August 30, 2018. Diabetes and prediabetes prevalence estimates were combined by the random–effects model. The existence of publication bias was tested by Egger regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 20 publications
3
68
1
Order By: Relevance
“…The results showed that the pooled prevalence of diabetes was 7.8% and the pooled prevalence of pre-diabetes was 10.1%. By comparing results with other developing countries, the pooled prevalence of diabetes in Bangladesh was shown to be lower than in Nepal 48 (8.4%) and Pakistan 49 (14.7%), while being higher than in Cameroon 50 (5.8%) and China 51 (6.3%). On the other hand, the pooled prevalence of pre-diabetes in Bangladesh was shown to be higher than in Cameroon 50 (7.1%) and lower than in Pakistan 49 (11.43%) and Nepal 48 (10.3%).…”
Section: Discussionmentioning
confidence: 82%
“…The results showed that the pooled prevalence of diabetes was 7.8% and the pooled prevalence of pre-diabetes was 10.1%. By comparing results with other developing countries, the pooled prevalence of diabetes in Bangladesh was shown to be lower than in Nepal 48 (8.4%) and Pakistan 49 (14.7%), while being higher than in Cameroon 50 (5.8%) and China 51 (6.3%). On the other hand, the pooled prevalence of pre-diabetes in Bangladesh was shown to be higher than in Cameroon 50 (7.1%) and lower than in Pakistan 49 (11.43%) and Nepal 48 (10.3%).…”
Section: Discussionmentioning
confidence: 82%
“…Pakistan also belongs to developing countries having sharp rise in diabetic type 2 patients. Meta-analysis of studies revealed high prevalence of diabetic (14.62%) and pre-diabetic individuals (11.43%) in Pakistan [ 3 ]. DM has become a challenge for human health and causes a significant loss to economic health as well [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the pooled prevalence of diabetes based on 10 population-based cross-sectional studies was 12.14%, with a total sample of 11,699 individuals. Compared with neighbouring countries sharing a similar lifestyle and culture, the pooled prevalence of diabetes in Afghanistan is higher than in Bangladesh (7.7%) [29] and Nepal (8.4%) [30], while lower than in India [31] and Pakistan (14.7%) [32].…”
Section: Discussionmentioning
confidence: 76%